Six new species of Anthuridae (Peracarida: Isopoda) from the southern Mexican Pacific - Jarquín-Martínez, Ubaldo; García-Madrigal, María del Socorro (European Journal of Taxonomy, 2021)
Marine isopods, despite being a very diverse group, have been little studied in the Mexican South Pacific. After a revision of 171 specimens collected from Guerrero and Oaxaca, six new species, belonging to five genera, were discovered: Amakusanthura guerrerensis sp. nov., Cortezura caeca sp. nov., Mesanthura antenniformis sp. nov., M. estacahuitensis sp. nov., Skuphonura oaxaquensis sp. nov., and Tinggianthura mexicana sp. nov. In this work, the genera Amakusanthura Nunomura, 1977 and Tinggianthura Chew, Abdul-Rahim & Haji Ross, 2014, are recorded for the first time in the Tropical Eastern Pacific. Also, the distribution range of the genus Skuphonura Barnard, 1925 is increased from the west coast of South America to the southern Mexican Pacific, this being the first record of this genus in the Mexican Pacific. This study doubles the number of species recorded of Anthuridae from the Mexican Pacific, of six to 12 species.